Pelaksanaan Multi Akad Pada Produk Gadai Emas Di Bank Syari’ah Perspektif Fiqh Mu’amalah (Studi Kasus Bank SUMUT Syari’ah Kantor Cabang Binjai) - Randitya Ahmad Basya; Muhammad Saleh; Khairani Sakdiah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
People are required to be able to keep up with the times. Economic activity and human needs as one of the most important aspects of human life are developing quite quickly and increasingly varied. This makes creativity in the development of transaction models and products increase. With various transaction models and products unknown in the past that aim to meet the needs of the community, this can also affect Islamic economic transaction activities by creating new products. This study aims to determine the implementation of multi-contracts in the perspective of fiqh muamalah on gold pawn products at Bank SUMUT Syari'ah Binjai Branch Office. This research was conducted by empirical research methods. The research approach used in this study is a qualitative approach. The data used in this study were primary data obtained from observations and interviews. The implementation of multi-contracts in gold pawn products at Bank SUMUT Syari'ah Binjai Branch Office is in accordance with applicable regulations. Then, the implementation of multi-contracts in gold pawn products from the perspective of fiqh mu'amalah is allowed by jumhur ulama.